C35 basalt fiber concrete for bridge abutment and preparation method of C35 basalt fiber concrete

By introducing a composite of mullite fiber and polycaprolactone melt into the basalt fiber concrete for abutment, an interlaced network structure is formed, which solves the problems of low interfacial bonding strength and cracking of basalt fiber concrete in the prior art in earthquake situations, and achieves high strength and good seismic resistance.

CN119822705AActive Publication Date: 2025-04-15HANZHONG MUNICIPAL HIGHWAY BUREAU

Patent Information

Application Number
CN202510085885.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-15
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

Existing basalt fiber concrete for abutment is prone to low interfacial bonding strength and cracking problems in earthquake situations, which affects the service life.

Method used

A composite material containing basalt fibers, mullite fibers and polycaprolactone melt is used to form an interlaced network structure through the viscosity of polycaprolactone and the flexibility of mullite fibers, thereby improving the bonding effect and seismic resistance.

Benefits of technology

It significantly improves the strength and seismic effect of concrete, reduces cracking caused by seismic waves, and extends the service life of abutment concrete.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of civil engineering materials, and particularly discloses C35 basalt fiber concrete for bridge abutments and a preparation method thereof.The C35 basalt fiber concrete for bridge abutments is prepared from 350-370 parts of cement, 170-185 parts of water, 570-620 parts of sand, 1140-1250 parts of gravel, 55-70 parts of fly ash, 40-55 parts of silica fume, 2-3.8 parts of a water reducing agent and 8-12 parts of a basalt fiber composite material. 6-8 parts of a waterproof agent and 3-6 parts of anti-seismic particles; the basalt fiber composite material is prepared from basalt fibers, mullite fibers and a polycaprolactone solution; the preparation method comprises the following steps: uniformly mixing the cement, the sand, the gravel, the fly ash, the silica fume and part of the water, adding the basalt fiber composite material, the anti-seismic particles and the waterproof agent, uniformly mixing, adding the water reducing agent and the rest of the water, uniformly mixing, pouring and curing to obtain the concrete. The material has the advantages of good shock resistance and high mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of civil engineering materials, and more specifically, to a C35 basalt fiber concrete for abutments and a preparation method thereof. Background Art

[0002] Abutments are buildings located at both ends of a bridge that support the superstructure of the bridge and connect to the embankment. Concrete materials commonly used in bridge construction need to have a certain bearing capacity. In recent years, adding different types of fiber materials to concrete has become one of the effective ways to improve the mechanical properties of concrete. Among them, basalt fiber has received widespread attention due to its excellent mechanical properties, corrosion resistance and environmental protection.

[0003] In the prior art, the Chinese invention patent document with publication number CN112159168A discloses a C35 basalt fiber concrete for abutments and a preparation method thereof, which comprises, by weight, 430-450 parts of cementitious material, 4 parts of basalt fiber, 1790-1800 parts of aggregate, 7-8 parts of water reducer, and 150-170 parts of water; wherein the cementitious material is composed of 280-300 parts of cement, 60-70 parts of fly ash, and 70-90 parts of slag powder.

[0004] Adding basalt fiber to existing concrete is prone to uneven fiber distribution, and basalt fiber in concrete only relies on the viscosity of cement to adhere to the inside of concrete, so basalt fiber in concrete is prone to low interfacial bonding strength. In the event of an earthquake, the basalt fiber on the abutment has limited affinity with the concrete cementitious material. Under the action of seismic waves, the cementitious material and gravel near the basalt fiber are prone to cracking during the vibration process, which can easily cause cracking in the concrete and affect the service life of the abutment.

[0005] Therefore, how to prepare a basalt fiber concrete with good seismic resistance and high mechanical strength for use in building abutments to extend the service life and durability of the abutments is a problem to be solved. Summary of the invention

[0006] In order to prepare a basalt fiber concrete with good seismic resistance and high mechanical strength for use in building abutments to extend the service life and durability of the abutments, the present application provides a C35 basalt fiber concrete for abutments and a preparation method thereof.

[0007] In the first aspect, the present application provides a C35 basalt fiber concrete for a bridge abutment, adopting the following technical scheme: a C35 basalt fiber concrete for a bridge abutment, the concrete comprising the following raw materials in parts by weight: 350-370 parts of cement, 170-185 parts of water, 570-620 parts of sand, 1140-1250 parts of crushed stone, 55-70 parts of fly ash, 40-55 parts of silica fume, 2-3.8 parts of water reducer, 8-12 parts of basalt fiber composite, 6-8 parts of waterproofing agent, and 3-6 parts of seismic resistant particles; the basalt fiber composite is made of basalt fiber, mullite fiber and polycaprolactone melt in a mass ratio of 1:0.2-0.4:0.2-0.3.

[0008] By adopting the above technical scheme, basalt fiber and mullite fiber are bonded by polycaprolactone melt to form an interlaced network bonding structure of basalt fiber and mullite fiber. The polycaprolactone on the surface of basalt fiber composite is insoluble in water and has a good dispersion effect. During the concrete mixing process, the problem of basalt fiber composite aggregation is not easy to occur, thereby ensuring that the basalt fiber is well distributed in the concrete. At the same time, the melting point of polycaprolactone is about 60°C. During the hydration process of large-volume concrete used for abutments, the hydration temperature can exceed 60°C, so that the polycaprolactone is gradually melted. The hot-melt polycaprolactone can not only improve the bonding effect between cement binder and basalt fiber composite, but also the bonding network with a large specific surface area formed by basalt fiber and mullite fiber can contact with the binder, further improving the bonding effect between basalt fiber composite and concrete binder, thereby improving the strength and seismic effect of concrete.

[0009] By utilizing the high strength and good tensile effect of basalt fiber, combined with the good flexibility and elasticity of mullite fiber and the flexibility of polycaprolactone, it can resist the pulling and shearing effect of earthquake transverse waves on concrete. At the same time, the flexibility and elasticity of mullite fiber combined with the network connection structure of basalt fiber composites, when the earthquake longitudinal wave reaches the surface of the abutment concrete, the earthquake longitudinal wave stretches the concrete, and the flexible network structure formed by polycaprolactone combined with the flexibility of mullite fiber can resist the tensile force and can deform appropriately with the tensile force. When the earthquake longitudinal wave generates compression force, the void compression effect of the network structure combined with the elasticity of mullite fiber can generate compression effect with the earthquake longitudinal wave, so that the concrete can maintain good stability under the tensile and compressive forces of the earthquake longitudinal wave, so that the concrete is not prone to cracking after being affected by the earthquake transverse wave and the earthquake longitudinal wave, thereby extending the service life of the abutment concrete.

[0010] Preferably, the basalt fiber is prepared by evenly spraying a rubber solution on basalt fiber filaments after oxygen plasma etching, and then evenly spraying a sucrose laurate solution on the basalt fiber filaments, and the mass ratio of the basalt fiber filaments to the rubber solution and the sucrose laurate solution is 1:0.2-0.35:0.1-0.2.

[0011] By adopting the above technical scheme, after the basalt fiber is etched by oxygen plasma, the surface roughness of the basalt increases, the surface porosity increases, and groups such as hydroxyl groups exist on the surface, and then the rubber solution is bonded. The roughness of the basalt fiber surface can increase the contact area between the basalt fiber and the rubber solution, and the hydroxyl groups on the surface of the basalt fiber and the viscosity of the rubber solution can further improve the bonding effect between the basalt fiber and the rubber solution. The flexibility and elasticity of the rubber solution are used to improve the flexibility and elasticity of the basalt fiber, so that the basalt fiber has higher strength in concrete while having certain flexibility and elasticity. When impacted by seismic waves, the basalt fiber, as the main supporting component, resists the shearing and pulling effect of the seismic transverse wave on the basalt, while the rubber enables the basalt fiber to resist the compression and stretching effect of the longitudinal wave, ensuring that the basalt fiber has higher stability when impacted by seismic waves.

[0012] The surface of basalt fiber is loaded with rubber and then bonded with sucrose laurate solution. The ester group in sucrose laurate is used to ensure that the basalt fiber has a good dispersion effect during the concrete mixing process and the dispersion uniformity of the basalt fiber in the concrete is guaranteed. The hydroxyl group in sucrose laurate is convenient for connecting with the cementitious material formed by cement. The hydroxyl group on the surface of the basalt fiber after oxygen etching further promotes the cross-linking and bonding of the basalt fiber and the cementitious material, and can improve the gradual connection effect of mortar and aggregate. The stable cross-linking connection network in the concrete makes it difficult for the concrete to crack when it is impacted by seismic waves, thereby ensuring the strength and durability of the concrete.

[0013] Preferably, the rubber solution is prepared from nitrile rubber, dimethylformamide and polyetheretherketone in a mass ratio of 1:100-120:0.2-0.6.

[0014] By adopting the above technical scheme, nitrile rubber and polyetheretherketone are dissolved in dimethylformamide, and the amide groups in dimethylformamide are easy to connect with the hydroxyl groups on the surface of basalt fiber filaments, and can also connect with the hydroxyl groups in sucrose laurate, thereby improving the cross-linking stability of the basalt fiber filaments and rubber, and cooperating with the sucrose laurate on the surface of the basalt fiber to bond with the cementitious material, further improving the bonding stability of the basalt fiber filaments, rubber and cementitious material, and improving the strength of concrete; at the same time, when subjected to earthquake shock waves, the basalt fiber resists shearing of transverse waves, and the rubber resists stretching and contraction of longitudinal waves. In the process of switching back and forth between transverse waves and longitudinal waves of earthquakes, the structural stability of concrete can still be maintained, thereby improving the earthquake resistance of concrete and extending the service life of concrete.

[0015] Preferably, the sucrose laurate solution is prepared from sucrose laurate, ethanol and cetearyl alcohol in a mass ratio of 1:90-110:0.2-0.5.

[0016] By adopting the above technical scheme, sucrose laurate and cetearyl alcohol are both soluble in ethanol but insoluble in water. During the concrete hydration process, they are not easy to absorb mixing water, thereby ensuring the hydration effect of cement and ensuring the uniformity of dispersion of basalt fiber in concrete.

[0017] During the hydration process, the melting point of cetearyl alcohol is around 50°C, and the hydration temperature of large-volume concrete used for abutments can reach up to around 70°C. After the cetearyl alcohol is hot-melted, the hydroxyl groups in the cetearyl alcohol, the hydroxyl groups in sucrose laurate, and the hydroxyl and amide groups on the surface of the basalt fiber are used to further improve the cross-linking and bonding effect between the basalt fiber and the cementitious material, thereby improving the bonding stability between the concrete cementitious material and the aggregate and the basalt fiber composite. When impacted by seismic waves, it can resist transverse and longitudinal waves, making it less likely for the concrete to crack, thereby extending the service life of the concrete.

[0018] Preferably, the mullite fiber is prepared by treating polycrystalline mullite fiber with ethyl glycolate and then uniformly spraying TPU liquid and ethyl formate particles, and the mass ratio of the polycrystalline mullite fiber, TPU liquid and ethyl formate particles is 1:0.2-0.3:0.1-0.2.

[0019] By adopting the above technical scheme, the porous structure of the polycrystalline mullite fiber is penetrated by ethyl glycolate, so that the pores on the surface of the mullite fiber are loaded with ethyl glycolate, and then bonded with TPU liquid, and the amino groups in the TPU liquid are attracted and connected with the hydroxyl groups in ethyl glycolate. Ethyl glycolate can also use its flexible chain segments to penetrate into the TPU molecular chain, further improving the flexibility of TPU; under the viscosity of the TPU liquid, the ethyl formate particles are adhered to the surface of the polycrystalline mullite fiber, and the amino and carboxyl groups in the ethyl formate are used to facilitate bonding with the adhesive. The cross-linking density and the bonding stability of the polycrystalline mullite fiber and the cementitious material are improved. When subjected to the impact of earthquake waves, the polycrystalline mullite fiber can resist the impact of longitudinal waves by utilizing its better flexibility and elasticity. Combined with the better impact effect of TPU, it can further resist the impact of longitudinal waves. The higher cross-linking density and better bonding stability can improve the polycrystalline mullite fiber's ability to resist the shear force of earthquake transverse waves, ensuring that the mullite fiber is not easily separated from the cementitious material, making it less likely for the concrete to crack during an earthquake, thereby extending the service life of the concrete.

[0020] Preferably, the TPU liquid is prepared from TPU, polyetheretherketone and dimethylformamide in a mass ratio of 1:0.2-0.5:90-120.

[0021] By adopting the above technical scheme, TPU and polyetheretherketone are both dissolved in dimethylformamide, and the hydroxyl group of ethyl glycolate on the surface of polycrystalline mullite fiber is connected with the amide group to improve the bonding effect of TPU on the surface of polycrystalline mullite fiber. The flexibility and elasticity of TPU are combined with the flexibility and strength of polyetheretherketone to improve the effect of polycrystalline mullite fiber in resisting seismic shear waves and longitudinal waves, thereby improving the seismic resistance of concrete and extending the service life of concrete.

[0022] Preferably, the shock-resistant particles are made of silica microspheres, polycarbonate microspheres and acetyl chitosan solution in a mass ratio of 1:0.5-1:0.4-0.6.

[0023] By adopting the above technical scheme, the bonding effect of acetyl glucosamine solution is utilized to make acetyl glucosamine adhere to the surface of silica microspheres and polycarbonate particles, and the amino and carboxyl groups of acetyl glucosamine are utilized to improve the cross-linking bonding effect between the seismic particles and the cementitious material and basalt fiber composite material, thereby improving the structural density of the concrete and making the concrete have better seismic resistance.

[0024] Preferably, the polycaprolactone melt is prepared from a polycaprolactone melt and urea particles in a mass ratio of 1:0.1-0.2.

[0025] By adopting the above technical scheme, urea particles are added to the polycaprolactone melt. During the concrete mixing process, the urea particles are not easy to absorb the mixing water, thereby ensuring the hydration effect of the concrete. During the hydration process, the large volume concrete used for the abutment has a high hydration temperature. After the polycaprolactone is hot-melted, the urea particles are gradually released. The urea particles absorb excess mixing water, and the amino groups in the urea can be interconnected with the cementitious material, basalt fiber, and mullite fiber to improve the internal structure density of the concrete, thereby improving the seismic effect of the concrete. At the same time, polycaprolactone has a certain viscosity and waterproof effect, which can further improve the seismic resistance and waterproofness of the concrete.

[0026] Preferably, the waterproofing agent is composed of silane coupling agent KH-570 and silicone waterproofing agent in a mass ratio of 1:0.5-1.

[0027] By adopting the above technical solution, the waterproof effect of concrete for abutments can be improved and the service life of concrete can be extended.

[0028] In a second aspect, the present application provides a method for preparing C35 basalt fiber concrete for abutments, using the following technical solution: A method for preparing C35 basalt fiber concrete for abutments comprises the following steps: S1. Weigh cement, sand, crushed stone, fly ash, silica fume, and 1 / 4-1 / 3 of the total amount of water, mix and stir evenly to obtain a primary mixture; S2, adding basalt fiber composite material, earthquake-resistant particles, and waterproofing agent to the primary mixture, mixing and stirring evenly to obtain a mixture; S3, add water reducing agent and 2 / 3-3 / 4 of the total water to the mixture, mix and stir evenly to obtain a mixed material; S4. The mixed materials are poured and cured to obtain finished concrete.

[0029] By adopting the above technical solution, a large volume of concrete for the abutment is obtained, which has higher strength and better earthquake resistance. Even after being impacted by earthquake waves, it is not prone to cracking, thereby extending the service life of the abutment concrete.

[0030] In summary, this application has the following beneficial effects: 1. The high strength and good tensile effect of basalt fiber, combined with the good flexibility and elasticity of mullite fiber and the flexibility of polycaprolactone, can resist the pulling and shearing effect of seismic shear waves on concrete. At the same time, the flexibility and elasticity of mullite fiber combined with the network connection structure of basalt fiber composites can keep the concrete stable under the tensile and compressive forces of seismic longitudinal waves, so that the concrete is not prone to cracking after being affected by seismic shear waves and longitudinal waves, thus extending the service life of the abutment concrete.

[0031] 2. The different lengths and sizes of basalt fibers ensure that the basalt fibers are evenly filled in the concrete. Combined with the size of the earthquake-resistant particles and the size of the mullite fibers, the concrete has a high filling density, which improves the density of the concrete while improving the earthquake-resistant effect of the concrete, thereby extending the service life of the concrete.

[0032] 3. The urea particles are filled with the viscosity of the polycaprolactone melt to facilitate the formation of a connection network for the basalt fiber composite. During the mixing process, the urea particles serve as support. In the later stage of hydration, the urea particles gradually dissolve in water, providing expansion space for the hydration of large-volume concrete, and promoting the contact between the concrete cementitious material and the basalt fiber composite, thereby increasing the contact area and thus improving the stability of the cross-linked structure and the seismic effect of the concrete. DETAILED DESCRIPTION

[0033] The present application is further described in detail below with reference to the embodiments.

[0034] Preparation example of basalt fiber The following raw materials and equipment are all commercially available.

[0035] Preparation Example 1: Basalt fiber is prepared by the following method: 1 kg of nitrile rubber and 0.5 kg of polyetheretherketone were added to 110 kg of dimethylformamide and stirred until they were completely dissolved to obtain a rubber solution; Add 1 kg of sucrose laurate and 0.4 kg of cetearyl alcohol to 100 kg of ethanol and stir until all dissolved to obtain a sucrose laurate solution; 1 kg of basalt fiber was subjected to oxygen plasma etching for 20 minutes to obtain etched basalt fiber, which consisted of basalt fiber with an average length of 10 mm and basalt fiber with an average length of 20 mm at a mass ratio of 1:0.5; 0.3 kg of rubber solution was evenly sprayed on the surface of the etched basalt fiber, the spraying speed of the rubber solution was 200 g / min, the etched basalt fiber was continuously stirred at a speed of 250 r / min during the spraying process, and the etched basalt fiber was dried and dispersed until the etched basalt fiber did not stick to each other and agglomerate to obtain loaded basalt fiber; 0.15 kg of sucrose laurate solution was evenly sprayed on the surface of the loaded basalt fiber, the spraying speed of the sucrose laurate solution was 200 g / min, the loaded basalt fiber was continuously stirred at a speed of 250 r / min during the spraying process, and the loaded basalt fiber was dried and dispersed until the loaded basalt fiber did not stick to each other and agglomerate to obtain basalt fiber.

[0036] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: 1 kg of nitrile rubber and 0.2 kg of polyetheretherketone were added into 100 kg of dimethylformamide and stirred until they were completely dissolved to obtain a rubber solution; 1 kg of sucrose laurate and 0.2 kg of cetearyl alcohol were added to 90 kg of ethanol and stirred until they were completely dissolved to obtain a sucrose laurate solution; 1 kg of basalt fiber was subjected to oxygen plasma etching for 20 minutes to obtain etched basalt fiber, which consisted of basalt fiber with an average length of 10 mm and basalt fiber with an average length of 20 mm at a mass ratio of 1:0.5; 0.2 kg of rubber solution was evenly sprayed on the surface of the etched basalt fiber, the spraying speed of the rubber solution was 200 g / min, the etched basalt fiber was continuously stirred at a speed of 250 r / min during the spraying process, and the etched basalt fiber was dried and dispersed until the etched basalt fiber did not stick to each other and agglomerate to obtain loaded basalt fiber; 0.1 kg of sucrose laurate solution was evenly sprayed on the surface of the loaded basalt fiber, the spraying speed of the sucrose laurate solution was 200 g / min, the loaded basalt fiber was continuously stirred at a speed of 250 r / min during the spraying process, and the loaded basalt fiber was dried and dispersed until the loaded basalt fiber did not stick to each other and agglomerate to obtain basalt fiber.

[0037] Preparation Example 3: This preparation example differs from Preparation Example 1 in that: 1 kg of nitrile rubber and 0.6 kg of polyetheretherketone were added to 110 kg of dimethylformamide and stirred until they were completely dissolved to obtain a rubber solution; Add 1 kg of sucrose laurate and 0.5 kg of cetearyl alcohol to 100 kg of ethanol and stir until all dissolved to obtain a sucrose laurate solution; 1 kg of basalt fiber was subjected to oxygen plasma etching for 20 minutes to obtain etched basalt fiber, which consisted of basalt fiber with an average length of 10 mm and basalt fiber with an average length of 20 mm at a mass ratio of 1:0.5; 0.35 kg of rubber solution was evenly sprayed on the surface of the etched basalt fiber, the spraying speed of the rubber solution was 200 g / min, and the etched basalt fiber was continuously stirred at a speed of 250 r / min during the spraying process, and the etched basalt fiber was dried and dispersed until the etched basalt fiber did not stick to each other and agglomerate to obtain loaded basalt fiber; 0.2 kg of sucrose laurate solution was evenly sprayed on the surface of the loaded basalt fiber, the spraying speed of the sucrose laurate solution was 200 g / min, and the loaded basalt fiber was continuously stirred at a speed of 250 r / min during the spraying process, and the loaded basalt fiber was dried and dispersed until the loaded basalt fiber did not stick to each other and agglomerate to obtain basalt fiber.

[0038] Preparation example of mullite fiber The following raw materials and equipment are all commercially available.

[0039] Preparation Example 4: Mullite fiber is prepared by the following method: 1kg of TPU and 0.4kg of polyetheretherketone are added to 100kg of dimethylformamide and stirred until completely dissolved to obtain TPU liquid; 1kg of polycrystalline mullite fiber is placed in 10kg of ethyl glycolate, the polycrystalline mullite fiber consists of fiber with an average length of 3mm and fiber with an average length of 5mm in a mass ratio of 1:0.5, ultrasonic dispersion is carried out at 20kHz for 30min, the polycrystalline mullite fiber is separated by filtration, and then 0.25kg of TPU liquid is evenly sprayed on the surface, and then 0.15kg of ethyl formate particles are added, and the average addition rate of ethyl formate particles is 200g / min. During the adding process, the polycrystalline mullite fiber is continuously stirred at a speed of 250r / min, and the finished mullite fiber is obtained by drying and dispersing until the polycrystalline mullite fiber does not stick to each other and agglomerate.

[0040] Preparation Example 5: This preparation example differs from Preparation Example 4 in that: 1kg of TPU and 0.2kg of polyetheretherketone are added to 90kg of dimethylformamide and stirred until completely dissolved to obtain TPU liquid; 1kg of polycrystalline mullite fiber is placed in 10kg of ethyl glycolate, the polycrystalline mullite fiber consists of fiber with an average length of 3mm and fiber with an average length of 5mm in a mass ratio of 1:0.5, ultrasonic dispersion is carried out at 20kHz for 30min, the polycrystalline mullite fiber is separated by filtration, and then 0.2kg of TPU liquid is evenly sprayed on the surface, and then 0.1kg of ethyl formate particles are added, and the average addition rate of ethyl formate particles is 200g / min. During the adding process, the polycrystalline mullite fiber is continuously stirred at a speed of 250r / min, and the finished mullite fiber is obtained by drying and dispersing until the polycrystalline mullite fiber does not stick to each other and agglomerate.

[0041] Preparation Example 6: This preparation example differs from Preparation Example 4 in that: 1kg of TPU and 0.5kg of polyetheretherketone are added to 120kg of dimethylformamide and stirred until completely dissolved to obtain TPU liquid; 1kg of polycrystalline mullite fiber is placed in 10kg of ethyl glycolate, the polycrystalline mullite fiber consists of fiber with an average length of 3mm and fiber with an average length of 5mm in a mass ratio of 1:0.5, ultrasonic dispersion is carried out at 20kHz for 30min, the polycrystalline mullite fiber is separated by filtration, and then 0.3kg of TPU liquid is evenly sprayed on the surface, and then 0.2kg of ethyl formate particles are added, and the average addition rate of ethyl formate particles is 200g / min. During the adding process, the polycrystalline mullite fiber is continuously stirred at a speed of 250r / min, and the finished mullite fiber is obtained by drying and dispersing until the polycrystalline mullite fiber does not stick to each other and agglomerate.

[0042] Preparation example of basalt fiber composite The following raw materials and equipment are all commercially available.

[0043] Preparation Example 7: Basalt fiber composite material is prepared by the following method: 1 kg of polycaprolactone was heated to 60 degrees Celsius to completely melt to obtain a polycaprolactone melt, 0.1 kg of urea particles were added to the polycaprolactone melt, the average particle size of the urea particles was 60 μm, and the addition rate of the urea particles was 200 g / min. During the addition process, the polycaprolactone melt was continuously stirred at a speed of 250 r / min, and after mixing and stirring evenly, a polycaprolactone melt was obtained; 0.25 kg of polycaprolactone melt was evenly sprayed on the surface of 1 kg of basalt fiber prepared in Preparation Example 1, and then 0.3 kg of mullite fiber prepared in Preparation Example 4 was added. The addition rate of the mullite fiber was 200 g / min. During the adding process, the basalt fiber was continuously stirred at a speed of 250 r / min. After the mixture was evenly stirred, it was dried and broken up to obtain a basalt fiber composite. The average particle size of the basalt fiber composite was 20-30 mm.

[0044] Preparation Example 8: This preparation example differs from Preparation Example 7 in that: 1 kg of polycaprolactone was heated to be completely melted to obtain a polycaprolactone melt, and 0.1 kg of urea particles were added at a rate of 200 g / min. During the addition process, the polycaprolactone melt was continuously stirred at a rate of 250 r / min. After being mixed and stirred evenly, a polycaprolactone melt was obtained; 0.2 kg of polycaprolactone melt was evenly sprayed on the surface of 1 kg of basalt fiber prepared in Preparation Example 2, and then 0.2 kg of mullite fiber prepared in Preparation Example 5 was added. The addition rate of the mullite fiber was 200 g / min. During the adding process, the basalt fiber was continuously stirred at a speed of 250 r / min. After the mixture was evenly stirred, it was dried and broken up to obtain a basalt fiber composite. The average particle size of the basalt fiber composite was 20-30 mm.

[0045] Preparation Example 9: This preparation example differs from Preparation Example 7 in that: 1 kg of polycaprolactone was heated until it was completely melted to obtain a polycaprolactone melt, and then 0.2 kg of urea particles were added at a rate of 200 g / min. During the addition process, the polycaprolactone melt was continuously stirred at a rate of 250 r / min. After being mixed and stirred evenly, a polycaprolactone melt was obtained; 0.3 kg of polycaprolactone melt was evenly sprayed on the surface of 1 kg of basalt fiber prepared in Preparation Example 3, and then 0.4 kg of mullite fiber prepared in Preparation Example 6 was added. The addition rate of the mullite fiber was 200 g / min. During the adding process, the basalt fiber was continuously stirred at a speed of 250 r / min. After the mixture was evenly stirred, it was dried and broken up to obtain a basalt fiber composite. The average particle size of the basalt fiber composite was 20-30 mm.

[0046] Preparation example of shock-resistant microparticles The following raw materials and equipment are all commercially available.

[0047] Preparation Example 10: Shock-resistant microparticles are prepared by the following method: 1 kg of silica microspheres and 1 kg of polycarbonate microspheres were weighed and mixed evenly to obtain mixed microspheres, wherein the average particle size of the silica microspheres was 20 μm, and the average particle size of the polycarbonate microspheres was 80 μm. 0.5 kg of acetyl glucosamine solution was evenly sprayed on the surface, wherein the acetyl glucosamine solution was an acetyl glucosamine aqueous solution with a mass fraction of 2%. The microspheres were dried and dispersed until they did not stick to each other and agglomerated, to obtain finished anti-seismic particles.

[0048] Preparation Example 11: This preparation example differs from Preparation Example 10 in that: 1 kg of silica microspheres and 0.5 kg of polycarbonate microspheres were weighed and mixed evenly to obtain mixed microspheres, and 0.4 kg of acetyl glucosamine solution was evenly sprayed on the surface, where the acetyl glucosamine solution was an acetyl glucosamine aqueous solution with a mass fraction of 2%. The microspheres were dried and dispersed until they did not stick to each other and agglomerated, to obtain finished anti-seismic particles.

[0049] Preparation Example 12: This preparation example differs from Preparation Example 10 in that: 1 kg of silica microspheres and 1 kg of polycarbonate microspheres were weighed and mixed evenly to obtain mixed microspheres, and 0.6 kg of acetyl glucosamine solution was evenly sprayed on the surface, where the acetyl glucosamine solution was an acetyl glucosamine aqueous solution with a mass fraction of 2%. The microspheres were dried and dispersed until they did not stick to each other and agglomerated, to obtain finished anti-seismic particles. Example

[0050] The following raw materials are all commercially available.

[0051] Example 1: C35 basalt fiber concrete for abutment: 360kg cement, 180kg water, 600kg sand, 1200kg crushed stone, 62kg fly ash, 48kg silica fume, 3kg water reducer, 10kg basalt fiber composite, 7kg waterproofing agent, 4.5kg earthquake-resistant particles; the water reducer is polycarboxylic acid high-efficiency water reducer; the basalt fiber composite is the basalt fiber composite prepared in Preparation Example 7; the earthquake-resistant particles are the earthquake-resistant particles of Preparation Example 10; the waterproofing agent is composed of silane coupling agent KH-570 and silicone waterproofing agent in a mass ratio of 1:1; the cement is ordinary silicate cement with a PO42.5; the particle size of the crushed stone is 5-25mm continuous grading, and the mud content is less than 1%; the sand is medium sand in Zone II, and the apparent density is 2660kg / m 3 , fineness modulus is 2.5, mud content is <1.0%; fly ash is F class II fly ash, fly ash fineness (45μm square hole sieve residue) is 8%, loss on ignition is <4.5%, water requirement ratio is <96%, water content is <0.2%; silica ash is SF93, silica content in silica ash is ≥86%, average particle size is 0.1-0.2μm, water content is <3%, loss on ignition is <5%, volcanic ash activity index is >92%, specific surface area is ≥15000m 2 / kg; The preparation method is as follows: S1. Weigh cement, sand, crushed stone, fly ash, mineral powder, and 1 / 3 of the total amount of water, mix and stir evenly to obtain a primary mixture; S2, adding basalt fiber composite material, earthquake-resistant particles, and waterproofing agent to the primary mixture, mixing and stirring evenly to obtain a mixture; S3, adding a water reducing agent and 2 / 3 of the total water to the mixture, mixing and stirring evenly to obtain a mixed material; S4. The mixed materials are poured and cured to obtain finished concrete.

[0052] Embodiment 2: This embodiment differs from Embodiment 1 in that: 350kg cement, 170kg water, 570kg sand, 1140kg crushed stone, 55kg fly ash, 40kg silica fume, 2kg water reducer, 8kg basalt fiber composite, 6kg waterproofing agent, 3kg earthquake-resistant particles; the basalt fiber composite is the basalt fiber composite prepared in Preparation Example 8; the earthquake-resistant particles are the earthquake-resistant particles prepared in Preparation Example 11; the waterproofing agent is composed of silane coupling agent KH-570 and silicone waterproofing agent in a mass ratio of 1:0.5; The preparation method is as follows: S1. Weigh cement, sand, crushed stone, fly ash, mineral powder, and 1 / 4 of the total amount of water, mix and stir evenly to obtain a primary mixture; S2, adding basalt fiber composite material, earthquake-resistant particles, and waterproofing agent to the primary mixture, mixing and stirring evenly to obtain a mixture; S3, adding a water reducing agent and 3 / 4 of the total amount of water to the mixture, mixing and stirring evenly to obtain a mixed material; S4. The mixed materials are poured and cured to obtain finished concrete.

[0053] Embodiment 3: This embodiment differs from Embodiment 1 in that: 370kg cement, 185kg water, 620kg sand, 1250kg crushed stone, 70kg fly ash, 55kg silica fume, 3.8kg water reducer, 12kg basalt fiber composite, 8kg waterproofing agent, 6kg earthquake-resistant particles; the earthquake-resistant particles are the earthquake-resistant particles of Preparation Example 12; the basalt fiber composite is the basalt fiber composite prepared in Preparation Example 9; the waterproofing agent is composed of silane coupling agent KH-570 and silicone waterproofing agent in a mass ratio of 1:1.

[0054] Embodiment 4: This embodiment differs from Embodiment 1 in that: The basalt fibers were not treated with oxygen plasma etching during preparation.

[0055] Embodiment 5: This embodiment differs from Embodiment 1 in that: No rubber solution was added during the preparation of basalt fiber.

[0056] Embodiment 6: This embodiment differs from Embodiment 1 in that: No sucrose laurate solution was added during the preparation of basalt fibers.

[0057] Embodiment 7: This embodiment differs from Embodiment 1 in that: The mullite fibers were not treated with ethyl glycolate during preparation.

[0058] Embodiment 8: This embodiment differs from Embodiment 1 in that: No TPU liquid was added during the preparation of mullite fibers.

[0059] Embodiment 9: This embodiment differs from Embodiment 1 in that: No urethane particles were added during the preparation of the mullite fibers.

[0060] Embodiment 10: This embodiment differs from Embodiment 1 in that: No acetyl glucosamine solution was added during the preparation of the shock-resistant microparticles.

[0061] Embodiment 11: This embodiment differs from Embodiment 1 in that: Urea fine particles are not added to the polycaprolactone melt.

[0062] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: The basalt fiber composite material was replaced by commercially available basalt fiber of equal quality in the raw materials.

[0063] Comparative Example 2: The difference between this comparative example and Example 1 is that: In the preparation process of the basalt fiber composite material, mullite fiber and polycaprolactone melt are not added in the raw materials.

[0064] Performance testing 1. Strength detection The methods of Examples 1-11 and Comparative Examples 1-2 were used to prepare concrete, and 1 m 3 For the test block, refer to GB / T50081-2016 to test the 28d strength of the curing and record the data.

[0065] 2. Earthquake resistance testing The methods of Examples 1-11 and Comparative Examples 1-2 were used to prepare concrete, and 1 m 3 For the test block, calculate the total cracking area per unit area 48 hours after pouring; subject the test block to an earthquake simulation vibration table to simulate the transverse and longitudinal waves generated by an earthquake. After processing for 30 minutes, continue to calculate the total cracking area per unit area and record the area difference = post-earthquake cracking area - pre-earthquake cracking area, and record the data.

[0066] Table 1 Performance test table project Compressive strength / MPa <![CDATA[Area difference / mm 2 / m 2 > Example 1 37.8 45.6 Example 2 37.5 47.2 Example 3 38.0 44.8 Example 4 37.2 50.5 Example 5 36.3 65.4 Example 6 36.6 61.3 Example 7 37.3 48.7 Example 8 36.5 63.9 Example 9 37.0 55.2 Example 10 36.0 75.5 Embodiment 11 36.7 58.4 Comparative Example 1 34.0 125.6 Comparative Example 2 35.2 92.3 It can be seen from Examples 1-3 and Table 1 that the concrete prepared in the present application has high strength, and after simulated earthquake treatment, the increased area of ​​cracks is small, indicating that the concrete has good earthquake resistance.

[0067] Combining Example 1 and Examples 4-11 and Table 1, it can be seen that the basalt fiber of Example 4 was not subjected to oxygen plasma etching during the preparation process. Compared with Example 1, the compressive strength of the concrete of Example 4 is less than that of Example 1, and the area difference of the cracks is greater than that of Example 1, indicating that after the basalt fiber is subjected to oxygen plasma etching, the roughness of the fiber surface can be increased, thereby facilitating the adhesion of rubber and sucrose laurate, improving the cross-linking effect of the basalt fiber and the cementitious material, and thus improving the strength and seismic resistance of the concrete.

[0068] In the preparation process of basalt fiber in Example 5, no rubber solution was added. Compared with Example 1, the compressive strength of concrete in Example 5 was lower than that in Example 1, and the difference in the area of ​​cracks was greater than that in Example 1, indicating that the addition of rubber can improve the flexibility of basalt fiber, thereby facilitating resistance to transverse and longitudinal waves of earthquakes and making the abutment have better seismic resistance.

[0069] In the preparation process of basalt fiber in Example 6, sucrose laurate solution was not added. Compared with Example 1, the compressive strength of concrete in Example 6 was lower than that in Example 1, and the difference in the area of ​​cracks was greater than that in Example 1, indicating that the addition of sucrose laurate solution can cross-link with the cementitious material and improve the density of the internal structure of the concrete, thereby improving the strength and seismic resistance of the concrete.

[0070] During the preparation of mullite fiber in Example 7, ethyl glycolate was not treated. Compared with Example 1, the compressive strength of concrete in Example 7 was less than that in Example 1, and the difference in the area of ​​cracks was greater than that in Example 1, indicating that ethyl glycolate can improve the flexibility of TPU, further improve the earthquake resistance and buffering effect of concrete, and promote the cross-linking of mullite fiber with cementitious materials and basalt fiber, thereby improving the density of concrete and making the concrete have higher strength and better earthquake resistance.

[0071] In Example 8, no TPU liquid was added during the preparation of the mullite fiber. Compared with Example 1, the compressive strength of the concrete in Example 8 was lower than that in Example 1, and the difference in the area of ​​the cracks was greater than that in Example 1, indicating that the addition of TPU can improve the flexibility and buffering effect of the mullite fiber, thereby improving the seismic resistance and strength of the concrete.

[0072] In Example 9, no ethyl formate particles were added during the preparation of the mullite fibers. Compared with Example 1, the compressive strength of the concrete in Example 9 was lower than that in Example 1, and the difference in the area of ​​the cracks was greater than that in Example 1, indicating that the ethyl formate particles could promote the cross-linking and bonding of the mullite fibers and the cementitious materials, thereby improving the seismic resistance and strength of the concrete.

[0073] No acetyl glucosamine solution was added during the preparation of the seismic microparticles in Example 10. Compared with Example 1, the compressive strength of the concrete in Example 10 was lower than that in Example 1, and the difference in the area of ​​cracks was greater than that in Example 1, indicating that acetyl glucosamine can improve the cross-linking effect of the seismic microparticles with cementitious materials and basalt fiber composites, and cooperate with the impact resistance and high toughness of the seismic microparticles, as well as their good filling effect, to further improve the structural density of the concrete, thereby improving the strength and seismic resistance of the concrete.

[0074] In Example 11, no urea particles are added to the polycaprolactone melt. Compared with Example 1, the compressive strength of the concrete in Example 11 is less than that in Example 1, and the difference in the area of ​​cracks is greater than that in Example 1, indicating that the urea particles are not easy to absorb mixing water during the mixing stage, thereby ensuring the hydration effect of the concrete. During the hydration process, the basalt fiber composite can promote the bonding between the basalt fiber composite and the cementitious material, and provide space for the pressure of seismic waves. The basalt fiber composite has the ability to resist the shear and tensile strength of seismic waves, thereby improving the seismic resistance of the concrete.

[0075] Combining Example 1 and Comparative Examples 1-2 and Table 1, it can be seen that the basalt fiber composite material in the raw material of Comparative Example 1 is replaced with commercially available basalt fibers of equal mass. Compared with Example 1, the compressive strength of the concrete in Comparative Example 1 is less than that in Example 1, and the difference in the area of ​​cracks is greater than that in Example 1, indicating that ordinary basalt fibers only have a filling effect and are filled in the concrete by relying on the viscosity of the cementitious material. During an earthquake, it is easy to cause cracks inside the concrete, affecting the strength of the concrete and thus affecting the service life of the abutment.

[0076] In the preparation process of the basalt fiber composite material in the raw materials of Comparative Example 2, no mullite fiber and polycaprolactone melt were added. Compared with Example 1, the compressive strength of the concrete in Comparative Example 2 was less than that in Example 1, and the difference in the area of ​​cracks was greater than that in Example 1, indicating that the combination of mullite fiber and polycaprolactone melt can resist the longitudinal waves of earthquakes, and cooperate with basalt fiber to resist the transverse waves of earthquakes, thereby improving the seismic effect of concrete and extending the service life of abutment concrete.

[0077] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A C35 basalt fiber concrete for abutment, characterized in that: The concrete comprises the following raw materials in parts by weight: 350-370 parts of cement, 170-185 parts of water, 570-620 parts of sand, 1140-1250 parts of crushed stone, 55-70 parts of fly ash, 40-55 parts of silica fume, 2-3.8 parts of water reducer, 8-12 parts of basalt fiber composite, 6-8 parts of waterproof agent, and 3-6 parts of earthquake-resistant particles; the basalt fiber composite is made of basalt fiber, mullite fiber and polycaprolactone melt in a mass ratio of 1:0.2-0.4:0.2-0.

3.

2. The C35 basalt fiber concrete for abutment according to claim 1, characterized in that: The basalt fiber is prepared by uniformly spraying a rubber solution and then a sucrose laurate solution on the basalt fiber yarn after oxygen plasma etching treatment. The mass ratio of the basalt fiber yarn to the rubber solution and the sucrose laurate solution is 1:0.2-0.35:0.1-0.

2.

3. The C35 basalt fiber concrete for abutment according to claim 2, characterized in that: The rubber solution is prepared from nitrile rubber, dimethylformamide and polyetheretherketone in a mass ratio of 1:100-120:0.2-0.

6.

4. The C35 basalt fiber concrete for abutment according to claim 2, characterized in that: The sucrose laurate solution is prepared from sucrose laurate, ethanol and cetearyl alcohol in a mass ratio of 1:90-110:0.2-0.

5.

5. The C35 basalt fiber concrete for abutment according to claim 1, characterized in that: The mullite fiber is prepared by treating polycrystalline mullite fiber with ethyl glycolate and then uniformly spraying TPU liquid and ethyl formate particles. The mass ratio of the polycrystalline mullite fiber, TPU liquid and ethyl formate particles is 1:0.2-0.3:0.1-0.

2.

6. The C35 basalt fiber concrete for abutment according to claim 5, characterized in that: The TPU liquid is prepared from TPU, polyetheretherketone and dimethylformamide in a mass ratio of 1:0.2-0.5:90-120.

7. The C35 basalt fiber concrete for abutment according to claim 1, characterized in that: The anti-vibration particles are prepared from silicon dioxide microspheres, polycarbonate microspheres and acetyl chitosan solution in a mass ratio of 1:0.5-1:0.4-0.

6.

8. The C35 basalt fiber concrete for abutment according to claim 1, characterized in that: The polycaprolactone melt is prepared from a polycaprolactone melt and urea particles in a mass ratio of 1:0.1-0.

2.

9. The C35 basalt fiber concrete for abutment according to claim 1, characterized in that: The waterproofing agent is composed of a silane coupling agent KH-570 and an organic silicon waterproofing agent in a mass ratio of 1:0.5-1.

10. The method for preparing C35 basalt fiber concrete for abutments according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh cement, sand, crushed stone, fly ash, silica fume, and 1 / 4-1 / 3 of the total amount of water, mix and stir evenly to obtain a primary mixture; S2, adding basalt fiber composite material, earthquake-resistant particles, and waterproofing agent to the primary mixture, mixing and stirring evenly to obtain a mixture; S3, add water reducing agent and 2 / 3-3 / 4 of the total water to the mixture, mix and stir evenly to obtain a mixed material; S4. The mixed materials are poured and cured to obtain finished concrete.

Citation Information

Patent Citations

  • C35 basalt fiber concrete for bridge abutment and preparation method of C35 basalt fiber concrete

    CN112159168A

  • Fiber aerogel foam concrete, preparation method and application thereof

    CN109231910A

  • High-performance concrete with low shrinkage

    CN113979712A

  • Anti-seismic and compressive concrete as well as preparation method and application thereof

    CN116535161A

  • Fiber-reinforced foamed polypropylene and preparation process thereof

    CN117209834A

Cited By

  • Aerated concrete block and lightweight heat-preservation sound-insulation composite block

    CN121609546A

  • Aerated concrete block and light thermal and sound insulation composite block

    CN121609546B